2012
DOI: 10.1080/00028487.2012.654890
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effect of Environmental Parameters on Feeding Ecology of the Shortnose Sturgeon in the Saint John River, New Brunswick

Abstract: We examined the effects of spatial, temporal, and environmental parameters on the feeding habits of the shortnose sturgeon Acipenser brevirostrum. We sampled sturgeon gut contents using colonic flushing, a new, low-impact technique. We found that heavy feeding continued until at least November, when water temperature reached 8 • C. In all seasons, foraging shortnose sturgeon used shallow water (2-8 m); however, in late fall this trend was even stronger, when 50% of the sturgeon were captured in less than 3 m d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…The recent colonization and domination of the SFE benthos by Corbula amurensis Schrenck, 1861 (the Asian overbite clam) (Feyrer et al 2003;Cloern and Jassby 2012) has displaced many of these prey species (Nichols et al 1990;Gilbert et al 2011;Greene et al 2011;Cloern and Jassby 2012). Other sturgeon species have been shown to successfully adjust their diet to altered prey availability (Brosse et al 2000;Usvyatsov et al 2012), and the Asian overbite clam has been identified as a major component of the diet of the sympatric white sturgeon (Kogut 2008). However, in sturgeons, manipulation of diet ration or nutritional content has been shown to affect growth, energetic status (Hung and Lutes 1987;Cui et al 1997;Hung et al 1997;Deng et al 2009;Han et al 2012;Haller et al 2015) and the cellular response to heat stress (Deng et al 2009;Han et al 2012;Wang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The recent colonization and domination of the SFE benthos by Corbula amurensis Schrenck, 1861 (the Asian overbite clam) (Feyrer et al 2003;Cloern and Jassby 2012) has displaced many of these prey species (Nichols et al 1990;Gilbert et al 2011;Greene et al 2011;Cloern and Jassby 2012). Other sturgeon species have been shown to successfully adjust their diet to altered prey availability (Brosse et al 2000;Usvyatsov et al 2012), and the Asian overbite clam has been identified as a major component of the diet of the sympatric white sturgeon (Kogut 2008). However, in sturgeons, manipulation of diet ration or nutritional content has been shown to affect growth, energetic status (Hung and Lutes 1987;Cui et al 1997;Hung et al 1997;Deng et al 2009;Han et al 2012;Haller et al 2015) and the cellular response to heat stress (Deng et al 2009;Han et al 2012;Wang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Usvyatsov et al. () found that freshwater bivalves were less digestible to Shortnose Sturgeon than softshell clams in saline waters of the Saint John River, New Brunswick, Canada. During spring on the Hudson River, the salt front is common in the Haverstraw Bay/Peekskill region, with the modeled salt front occurring north of Peekskill on average 61% (SD = 34%) of the time during the study period (Georgas and Blumberg ; Urban Ocean Observatory at Davidson Laboratory ).…”
Section: Discussionmentioning
confidence: 99%
“…Shortnose Sturgeon are opportunistic suction feeders, exploiting deepwater channel habitats (Dadswell ; Carlson and Simpson ; Bain ; Usvyatsov et al. ). Within this 75‐km stretch, tagged fish were mostly detected in channel habitats (>5 m) comprising mud and sand sediments.…”
Section: Discussionmentioning
confidence: 99%
“…Riverine habitats typically used by juveniles and adults follow: sandy to hard‐mud bottom; water depth – highly variable from channel to shoals, with night‐time foraging often in water <1 m deep; but no diel pattern of water depth use by CR SNS (Kynard et al., ). However, SJohnR SNS have a seasonal difference in foraging depth where the shallowest depths are used in the fall (Usvyatsov et al., ). Thus, GOM and northeastern SNS are highly flexible for foraging depth with fish probably going wherever forage is most abundant.…”
Section: Habitat Requirements Preferences Foraging and Tolerancesmentioning
confidence: 99%
“…Juveniles and adults are characterized as benthic cruising predators with a broad diet, foraging opportunistically on a wide variety of invertebrates like benthic insects, crustaceans, mollusks, and polychaetes (Taubert, ; Dadswell et al., ; Kynard, ; Usvyatsov et al., ). Forage items vary widely depending on their abundance in space and time.…”
Section: Habitat Requirements Preferences Foraging and Tolerancesmentioning
confidence: 99%